2020
DOI: 10.2196/16961
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Effectiveness and Motivations for the Use of Web-Based Mental Health Programs: Qualitative Study

Abstract: Background The prevalence of depression is high and has been stable despite increased treatment, research, and dissemination. People encounter barriers to seeking traditional mental health services, which could be mitigated by using web-based prevention methods. Objective This study aims to understand what people at high risk for depression perceive as effective aspects of web-based mental health programs and what motivates people at high risk for depre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Other program functionality issues were also evident, highlighting the importance of a user-friendly design and interface. In addition, many HardHat participants did not receive the reminder emails that were sent, thus limiting their effectiveness [ 8 ]. The qualitative results also shed light on the importance of program personalization and balancing text and video and audio content, and these findings should be taken into consideration in the design of future digital mental health programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other program functionality issues were also evident, highlighting the importance of a user-friendly design and interface. In addition, many HardHat participants did not receive the reminder emails that were sent, thus limiting their effectiveness [ 8 ]. The qualitative results also shed light on the importance of program personalization and balancing text and video and audio content, and these findings should be taken into consideration in the design of future digital mental health programs.…”
Section: Discussionmentioning
confidence: 99%
“…Web-based mental health programs can play an important role in the prevention of depression by increasing accessibility, confidentiality, and sustainability [ 6 ], and those based on cognitive behavioral therapy (CBT) have been shown to be effective at decreasing stress [ 7 ]. A recent study found that web-based mental health programs were perceived by users to increase both individual and societal mental health awareness [ 8 ]. However, the rates of use and adherence to such programs can be low and inconsistent, with completion rates in randomized controlled trials (RCTs) ranging from 14% to 90% [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study of 93 mobile mental health apps showed that the overall user retention is very low, with a 15-day retention rate of 3.9% and a 30-day retention rate of 3.3% [ 16 ]. Another study with 77 participants in two randomized controlled trials demonstrated how difficult it is to motivate people to begin using an e-mental health solution [ 17 ]. Any digital health trial will see a significant proportion of users drop out or cease using the app before completion.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary research suggests music therapy via telehealth improves access to care and community music engagement [14,15]. Research also suggests web-based services are promising avenues to increase mental health awareness and treatment options [16,17]. For those practicing via mediated technologies, there are several freely available and fee-based platforms to choose from, including Doxy.me (Doxy.me LLC, Rochester, NY), Microsoft Teams (Microsoft Corporation, Redmond, WA), Skype for Business (Microsoft Corporation), WebEx (Webex by Cisco, Milpitas, CA), and Zoom (Zoom Video Communications Inc, San Jose, CA).…”
Section: Introductionmentioning
confidence: 99%